Polemik Pandemik Covid-19 dan Implikasinya Terhadap Kesehatan Jiwa - Mukniah Mukniah (IJIP : Indonesian Journal of Islamic Psychology, 2020)
Abstract  The debate about the issue of Covid-19 that was spread in the mass media into a polemic has not been resolved in the community. The Covid-19 virus was first reported on December 29, 2019 in Wuhan City, Hubai Province, China. Overall, not only does it have an impact on physical health aspects, the impact of shocks also impacts on mental health. The purpose of this study was to analyze the mental health condition resulting from the covid-19 coverage through the mass media. This pandemic must be understood as an opportunity for the community to actualize themselves into new things, in accordance with policies recommended by the government. So it does not cause emotional shocks which result in shocks to mental health.Abstrak Perdebatan mengenai isu Covid-19 yang tersebar di media massa menjadi polemik belum terselesaikan di masyarakat. Virus Covid-19 pertama kali dilaporkan pada 29 Desember 2019 di kota Wuhan, Propinsi Hubai, China. Secara keseluruhan, tidak hanya memberikan dampak pada aspek kesehatan fisik saja, akibat dari guncangan juga berimbas pada kesehatan jiwa. Tujuan dari penelitian ini untuk menganalisa kondisi kesehatan jiwa yang diakibatkan dari pemberitaan covid-19 melalui media massa.  Pandemi ini harus dipahami sebagai kesempatan bagi masyarakat untuk mengaktualisasikan diri ke dalam hal-hal baru, sesuai dengan kebijakan yang dianjurkan pemerintah. Sehingga tidak menimbulkan guncangan emosional yang mengakibatkan tekanan jiwa atau gangguan jiwa.